Tumor board review : guideline and case reviews in oncology - Todd, Robert F., III; Cooney, Kathleen A.; Hayes, Teresa G.; Mims, Martha Pritchett; Worden, Francis P. (Demos Medical, 2015)
Praise for the First Edition: "As everyone in oncology fellowship training knows, there is a huge [information] gap in this field. Most oncology books are massive and loaded with information by the time the book is [published] it is outdated." [Tumor Board Review] is fresh and just out of the oven I haven't seen any book in oncology like this so far I think my investment in this book was wise and worth it."--Humaid Al- Shamsi, MB(Hon), BMedSc, MRCP(UK), FRCP, FACP, Assistant Professor, The University of Texas, MD Anderson Cancer Center Culling the knowledge and expertise of respected oncology specialists, this is a concise yet comprehensive review of all areas of oncology practice for medical oncologists, radiation oncologists, and pathologists--both students and practitioners. The second edition of Tumor Board Review has been thoroughly revised to encompass recent scientific advances in assessment and treatment, new clinical guidelines, and new FDA-approved drugs and indications. It also contains approximately 350 multiple-choice questions and answers to assist readers in testing their knowledge, especially those preparing for the MOC exam. The book features case presentations and evidence-based management discussions that clearly demonstrate how to apply new information in daily practice. In a consistent format, each chapter addresses epidemiology, risk factors, natural history, and pathology of each major organ-specific tumor type; an abbreviated display of relevant staging; and several "tumor board style" illustrative patient case studies. This is followed by an evidence-based case discussion, which reinforces current guidelines and explains the rationale for the diagnostic and therapeutic steps taken. Algorithms and decision-tree graphics further illuminate the decision process. New to the Second Edition of Tumor Board Review: Revised and updated with state-of-the-art knowledge Presents the most recent guidelines and management. -- Rittenhouse.